Piezoelectric Shells Sensing, Energy Harvesting, and Distributed Control-Second Edition - Tzou, Hornsen (HS).; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2019)
This book offers an introduction to piezoelectric shells and distributed sensing, energy harvesting and control applications. It familiarizes readers with a generic approach of piezoelectric shells and fundamental electromechanics of distributed piezoelectric sensors, energy harvesters and actuators applied to shell structures. The book is divided into two major parts, the first of which focuses on piezoelectric shell continua, while the second examines distributing sensing, energy harvesting and control of elastic continua, e.g., shells and plates. The exploitation of new, advanced multifunctional smart structures and structronic systems has been one of the mainstream research and development activities over the years. In the search for innovative structronics technologies, piezoelectric materials have proved to be very versatile in both sensor and actuator applications. Consequently, the piezoelectric technology has been applied to a broad range of practical applications,from small-scale nano- and micro-sensors/actuators to large-scale airplane and space structures and systems. The book provides practicing engineers and researchers with an introduction to advanced piezoelectric shell theories and distributed sensor/energy harvester/actuator technologies in the context of structural identification, energy harvesting and precision control. The book can also be used as a textbook for graduate students. This second edition contains substantial new materials, especially energy harvesting and experimental components, and has been updated and corrected for a new generation of readers. .
Piezoelectric Shell Vibration Theory -- Common Piezoelectric Continua and Active Piezoelectric Structures -- Distributed Sensing and Control of Elastic Shells (with new material added) -- Multi-Layered Shell Actuators -- Boundary Control of Beams.-Distributed Control of Plates with Segmented Sensors and Actuators -- Convolving Shell Sensors and Actuators Applied to Rings -- Sensing and Control of Cylindrical Shells -- Finite Element Formulation and Analyses.
Keywords: Automotive engineering; Electrical engineering; Automotive Engineering; Electrical and Electronic Engineering